Induced spawning trial with Ariopsis seemanni (Orinoquia, 2019)
The tete sea catfish Ariopsis seemanni is a fish used for human consumption by fishermen and residents along the coast of Colombia and as ornamental fish (5 to 10 cm –total longitude), at national and international comercial level. In Colombia, this species has been prioritized in the national aquaculture research agenda 2011-2012, as one of the potential marine species for aquaculture activities. This research was aimed at evaluating the effect of human chorionic gonadotropin (HGC) and carp pituitary extract (EPC) on final maturation and spawning adult females of the species. 24 pairs of wild fish were used, with an average weight of 263.6±42.2 g and 174.4±30.4 g for females and males, respectively. Four hormonal treatments was be used: T1: EPC 5 mg/kg; T2: EPC 7 mg/kg; T3: HGC 2000 IU/kg and T4: HGC 1000 IU/kg. Identify three types of maturation oocytes was. There were no statistically significant differences (p>0,05) between treatments used and the number of oocytes achieving maturation. No spontaneous spawning was obtained in any of the females induced with the hormonal doses used.
Keywords: HGC; EPC; Bagre; Canchimalo